2021
DOI: 10.1111/jdi.13733
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal volume index trajectories and risk of diabetes mellitus: Results from the China Health and Nutrition Survey

Abstract: Aims/Introduction Abdominal obesity is a risk factor for developing diabetes mellitus, but trajectories of abdominal obesity over time and incident diabetes mellitus have not been considered. We derived trajectories of abdominal volume index (AVI) over 16 years of follow up, and examined the associations between AVI trajectories and risk of diabetes mellitus. Materials and Methods Data were used from the China Health and Nutrition Survey, and 5,267 participants were enrolled to fit the trajectory of AVI by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The China Health and Nutrition Survey (CHNS) is an ongoing longitudinal community-based cohort study carried out by the national and local governments of China, and the study details were described in our previous article [25]with the relevant protocol published elsewhere [26]. The CHNS is a collaborative project between the Carolina Population Center, University of North Carolina at Chapel Hill and the National Institute for Nutrition and Health (NINH, former National Institute of Nutrition and Food Safety), Chinese Center for Disease Control and Prevention.…”
Section: Study Setting and Populationmentioning
confidence: 99%
“…The China Health and Nutrition Survey (CHNS) is an ongoing longitudinal community-based cohort study carried out by the national and local governments of China, and the study details were described in our previous article [25]with the relevant protocol published elsewhere [26]. The CHNS is a collaborative project between the Carolina Population Center, University of North Carolina at Chapel Hill and the National Institute for Nutrition and Health (NINH, former National Institute of Nutrition and Food Safety), Chinese Center for Disease Control and Prevention.…”
Section: Study Setting and Populationmentioning
confidence: 99%
“…However, their association with dietary consumption has not received much attention. Hu and coworkers discovered that a higher AVI was associated with higher energy intake when they calculated AVI trajectories over the course of 16 years of follow‐up and examined the associations between these trajectories and the risk of diabetes mellitus (Hu et al, 2022). Similarly, do Prado et al, reported that the consumption of ultra‐processed food was one of the primary causes of CI elevation and that CI had strong discriminatory power for the diagnosis of abdominal obesity among rural workers (do Prado et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For predicting metabolic syndrome in a similar study by Duan et al, AVI had the AUC of 0.838 and 0.794 for men and women, respectively [ 50 ]. In a study by Hu et al, AVI, as an index for abdominal adiposity, was associated with diabetes mellitus [ 29 ]. In a study by Hajian-Tilaki et al, they demonstrated that AVI and WC had the same mean between males and females, while the means of BMI and WHtR were different between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal volume index (AVI) is another novel anthropometric index and indicator of central obesity that is shown to be correlated with diabetes mellitus and metabolic abnormalities [26][27][28]. AVI has been suggested as a screening tool for metabolic syndrome of adulthood in diferent populations [29,30].…”
Section: Introductionmentioning
confidence: 99%